Recent Advances of 4D Printing Technologies Toward Soft Tactile Sensors - Tang, Yuneng; Dai, Baiqian; Su, Bin; Shi, Yusheng (Frontiers in Materials, 2021)
Soft tactile sensors combine the flexibility and the converting ability between mechanical forces and electrical signals. 4D printing was first introduced in 2013 and attracted great interest because of its versatile functionalities in actuators, artificial muscles, soft tactile sensors, soft energy harvesting, pneumatic nets, electroactive polymers, and soft electronics. Using the 4D printing concept to fabricate soft tactile sensors is promising yet at its infant stage. At present, researchers have utilized two kinds of strategies, one is directly using smart materials through 3D printing manufacturing, and the other is programming codes of components and structures to create controllable changes. This review summarizes the recent research on 4D printing towards soft tactile sensors and discusses future perspectives for this emerging field.